2011
DOI: 10.1258/ijsa.2011.010525
|View full text |Cite
|
Sign up to set email alerts
|

Particular clinical presentations of psoriasis in HIV patients

Abstract: Patients with HIV infection have a higher propensity for infectious, inflammatory, neoplastic and metabolic disorders. The link with psoriasis vulgaris is explained by well-known pathophysiological phenomena and can be observed at any stage of infection. The aim of our study was to characterize the clinical spectrum of psoriasis in a group of 50 patients with HIV. Our findings showed particular clinical presentations of psoriasis in those patients, suggesting a predilection for scalp lesions, palmoplantar kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
1
18
1
2
Order By: Relevance
“…Our results showed that the HCP5 gene was associated with psoriasis in Chinese at both genotypic and allelic level, which is in line with the findings from European studies (Capon et al ., ; Fernandes et al ., ). Our observation indicates that the HCP5 ‐G allele is a risk allele for psoriasis (OR = 4.61).…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed that the HCP5 gene was associated with psoriasis in Chinese at both genotypic and allelic level, which is in line with the findings from European studies (Capon et al ., ; Fernandes et al ., ). Our observation indicates that the HCP5 ‐G allele is a risk allele for psoriasis (OR = 4.61).…”
Section: Discussionmentioning
confidence: 98%
“…HIV infection is characterized by a progressive decrease in CD4 + T‐cell count, and it could seem paradoxical that psoriasis exacerbations are more frequent in this subset of patients than the general population, even though it is commonly observed at any stage of infection (De Simone, Perino, Caldarola, D'Agostino, & Peris, ; Fernandes et al, ; Klein et al, ; Morar et al, ; Parker, ). On the other hand, the HIV infection is also characterized by an increased CD8 + T‐cell number, leading to an inverted CD4 + /CD8 + ratio suggestive of a chronic inflammatory status, which could lead to the onset of psoriasis (De Simone et al, ; Fernandes et al, ; Klein et al, ; Morar et al, ; Parker, ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Psoriasis is a frequent reason for a dermatologist consultation. Its onset in otherwise healthy individuals should raise suspicion of a HIV infection when particular aspects, such as multiple subtypes, and risk factors are present (Fernandes et al, ; Khambaty & Hsu, ). As a matter of fact, cutaneous manifestations may onset for the first time or exacerbate when the CD4+ T‐cell number severely decreases with the HIV infection progression (Morar et al, ).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Despite the availability of various treatment modalities, psoriasis in the context of HIV tends to have a chronic-recurrent character and high failure rates. (12) However, even in the face of these difficulties, treatment should still be instituted for psoriasis and other dermatologic and rheumatologic disorders afflicting patients with HIV, as these disorders may be severely troubling to patients and adversely affect their quality of life. HIV infection, in order to facilitate early diagnosis and treatment, which will ultimately improve patient outcome.…”
Section: Ca S E R Epo Rtmentioning
confidence: 99%